A new quasi-dynamic method for the prediction of tendon tension of TLP platform. (15th February 2023) - Huang, Wei; Li, Binbin; Chen, Xiaobo
Abstract: The assessment of tendon mechanics for the tension leg platform (TLP) is crucial to the safety of the whole TLP system. The tendon design includes nonlinear mechanical characteristics such as set-down and various dynamic effects such as slow drift and springing. In this study, a new quasi-dynamic method dedicated to the dynamic tension of tendon and global motion of TLP is established by employing two primary assumptions, i.e. the separation of the hull's horizontal and vertical response, and the separation of low-frequency, wave-frequency, and high-frequency excitations due to waves. An analytical tendon model is proposed, and the simultaneous time history of tendon tension can be obtained through the post-treatment after carefully handling the hull's various dynamic responses. A remarkable efficiency is achieved since the time-consuming convolution integral, finite element model of the tendon, etc., are avoided. A comprehensive validation regarding the TLP system, global motion, and tendon tension is conducted by the comparisons with model test measurement and fully coupled analysis using OrcaFlex. An excellent agreement is achieved no matter the cycles and phases in the time series or the extremes in the statistics. The study has proven the quasi-dynamic method a reliable approach with satisfactory accuracy and superb efficiency, which should be a useful method in the design of the TLP platform. Highlights: A new quasi-dynamic method is established for TLP tendon tensions and global motions. Simultaneous tendon tension is obtained by the analytical model and global motions are predicted in the time domain. Comparisons between quasi-dynamic and fully coupled methods are carried out. The quasi-dynamic method is proven as a reliable and efficient numerical tool in the design.